Seawater‐Based Biocatalytic Strategy: Stereoselective Reductions of Ketones with Marine Yeasts. Issue 20 (15th September 2016) - Serra, Immacolata; Guidi, Benedetta; Burgaud, Gaetan; Contente, Martina L.; Ferraboschi, Patrizia; Pinto, Andrea; Compagno, Concetta; Molinari, Francesco; Romano, Diego
Abstract: The large consumption of freshwater in fermentations and bio‐transformations is a matter of concern for the sustainability of many bio‐processes. The use of seawater to perform bio‐processes is a sustainable alternative. In this work, we used marine yeasts from deep‐sub‐seafloor sediments grown in seawater as bio‐catalysts to perform the stereoselective reduction of different ketones, and the bio‐transformations were accomplished in seawater as well. Strains of Meyerozyma guilliermondii and Rhodotorula mucilaginosa were able to reduce different aromatic ketones with high molar conversions and moderate‐to‐high enantioselectivity with no significant differences between bio‐catalysis performed in seawater and freshwater. Finally, the selected marine yeasts were used for the reduction of key intermediates in seawater for the synthesis of molecules of pharmaceutical interest (desogestrel, norgestrel, gestodene, pramipexole). Abstract : All at sea : Marine yeasts from deep‐sub‐seafloor sediments were grown in seawater and used as biocatalysts to perform the stereoselective reduction of different ketones in seawater as well. Strains of Meyerozyma guilliermondii and Rhodotorula mucilaginosa were able to reduce different aromatic ketones with high molar conversions and moderate‐to‐high enantioselectivity.